Climate and host‐plant associations shaped the evolution of ceutorhynch weevils throughout the Cenozoic. (10th August 2018) - Letsch, Harald; Gottsberger, Brigitte; Metzl, Christian; Astrin, Jonas; Friedman, Ariel L. L.; McKenna, Duane D.; Fiedler, Konrad
Abstract: Using molecular phylogenetic data and methods we inferred divergence times and diversification patterns for the weevil subfamily Ceutorhynchinae in the context of host‐plant associations and global climate over evolutionary time. We detected four major diversification shifts that correlate with both host shifts and major climate events. Ceutorhynchinae experienced an increase in diversification rate at ∼53 Ma, during the Early Eocene Climate Optimum, coincident with a host shift to Lamiaceae. A second major diversification phase occurred at the end of the Eocene (∼34 Ma). This contrasts with the overall deterioration in climate equability at the Eocene‐Oligocene boundary, but tracks the diversification of important host plant clades in temperate (higher) latitudes, leading to increased diversification rates in the weevil clades infesting temperate hosts. A third major phase of diversification is correlated with the rising temperatures of the Late Oligocene Warming Event (∼26.5 Ma); diversification rates then declined shortly after the Middle Miocene Climate Transition (∼14.9 Ma). Our results indicate that biotic and abiotic factors together explain the evolution of Ceutorhynchinae better than each of these drivers viewed in isolation.